ATRX function beyond hippocampal CA1 is required for cognitive deficits in mouse models of intellectual disability - Julia T. Brott; Nathalie G. Bérubé (PLoS ONE, 2026)
ATR-X syndrome, caused by mutations in the ATRX gene, leads to intellectual disability and neurodevelopmental deficits, with previous mouse models implicating forebrain ATRX loss in cognitive impairment. However, the region-specific requirements of neuronal ATRX for cognitive function remain unclear. Here, we generated conditional knockout mice with predominant deletion of ATRX in hippocampal CA1 pyramidal neurons in both pure C57Bl/6J and hybrid C57Bl/6J + 129S2/Sv genetic backgrounds. Immunofluorescence confirmed efficient ATRX loss in CA1 neurons, with mosaic expression throughout other forebrain structures. Behavioral analyses revealed that T29-1 CaMKIIα-Cre ATRX knockout mice exhibited significant hypoactivity and increased anxiety traits, particularly in the open field, but retained normal hippocampal-dependent contextual fear memory and spatial learning and memory. In contrast, we confirmed that mice with robust forebrain-wide ATRX ablation in excitatory neurons (R1ag#5 CaMKIIα-Cre-mediated) displayed deficits in these cognitive domains. Our findings demonstrate that ATRX-related intellectual disability requires disruption of broader hippocampal or forebrain circuits to elicit cognitive impairments in learning and memory.